Method for constructing titanium alloy heterostructure in situ by mixing alpha-rich and beta-rich powders
Patent Information
- Application Number
- CN202611269607.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-20
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2046-08-20
AI Technical Summary
[0007]本申请的目的在于提供一种富α与富β双粉末混合原位构筑钛合金异质结构的方法,利用增材制造的非平衡凝固以及熔池中马兰戈尼运动的物理混合特点,将“极端非平衡的微区快速凝固与微偏析”这一本征冶金缺陷转化为可控的微观组织调控手段,在解决增材制造的柱状晶外延生长与成分不均匀等本征冶金缺陷的同时,具有工业生产的可实施性与可扩展性,是一种可规模化、低门槛、可复制的钛合金增材制造材料-工艺一体化解决方案
本申请利用双粉末物理混合与激光定向能量沉积相结合的方法,将富α稳定元素的钛合金粉末(粉末A)、富β稳定元素的钛合金粉末(粉末B)直接掺混打印,利用熔池非平衡凝固的特点,转化增材制造中“微观偏析”劣势为“成分调制”优势。该方法颠覆传统依赖热处理调控的常规思路,实现以非平衡促设计,无需复杂后处理即可获得优异的组织与力学性能协同。通过预制混粉沉积直接制备异构材料,无需多料仓配粉或复杂送粉系统,工艺链短且设备改造要求低。该方法工业柔性高、适应性广,除钛合金外对其他相变合金同样有效,极易在现有生产线快速导入,极其利于低成本的工程化与大批量生产应用。
Smart Images

Figure CN122769463B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of lightweight alloy preparation and hot working technology, and in particular to a method for in-situ construction of titanium alloy heterostructures by mixing α-rich and β-rich dual powders. Background Technology
[0002] Titanium alloys possess advantages such as high specific strength, good corrosion resistance, and excellent high-temperature mechanical properties, and are widely recognized as key structural materials with great development potential in cutting-edge fields such as aerospace, marine engineering, and energy and chemical engineering. Additive manufacturing technology, with its advantages of high forming efficiency and good processing flexibility, has become the core process for manufacturing large and complex titanium alloy load-bearing components. However, the microstructure formation mechanism of additively manufactured titanium alloys differs fundamentally from that of traditional castings and forgings. Its solidification process is dominated by extreme non-equilibrium thermophysical conditions, making it far from sufficient to rely solely on traditional heat treatment after forming to control the microstructure. During laser additive manufacturing, the extremely high temperature gradient and rapid cooling rate lead to the strong textural growth of coarse epitaxial columnar crystals; simultaneously, the extremely short solidification time within the tiny molten pool prevents alloying elements from fully diffusing, resulting in unavoidable "microscopic segregation." Even with subsequent long-term homogenization annealing or hot isostatic pressing, it is difficult to fundamentally eliminate the severe anisotropy and performance dispersion problems caused by the solidification structure, and grain coarsening often leads to a significant decrease in strength, making it impossible to achieve simultaneous improvement in strength and plasticity. Therefore, how to break the epitaxial growth of columnar crystals in situ during the printing stage and achieve synergistic optimization of microstructure and properties is crucial for improving the engineering applications of additive manufacturing titanium alloys.
[0003] Currently, research on suppressing columnar grains and refining the microstructure of additively manufactured titanium alloys mainly focuses on the following aspects: (1) Powder modification and in-situ alloying: Titanium alloy powder is mixed with oxide, nitride and other powders and then subjected to selective laser melting to form in-situ alloying by oxide reduction or nitride decomposition. For example, CN119733848A mixes titanium alloy powder with TiO2 powder and then uses selective laser melting to form in-situ alloy, which reduces the anisotropy of alloy properties and improves tensile strength. However, this method has strict requirements for the control of TiO2 addition. When the oxygen content exceeds 0.5%, the elongation of the material will decrease significantly, and it is not suitable for alloy systems containing highly active elements such as V, Y and La.
[0004] (2) Ultrasonic-assisted additive manufacturing: This involves introducing ultrasonic vibration to interfere with the solidification behavior of the molten pool. For example, CN119634891A discloses an arc additive manufacturing method for refining titanium alloy grains with coaxial ultrasonic assistance, which can achieve grain refinement and uniform distribution of titanium alloys. However, this method relies on special ultrasonic equipment, the process is complex, and the ultrasonic effect is mainly limited to the molten pool, making it difficult to eliminate the intrinsic thermal cycling effect of additive manufacturing.
[0005] (3) Alloying modification treatment: By adding specific alloying elements or ceramic particles to titanium alloys, the transformation of columnar crystals to equiaxed crystals is promoted by the supercooling effect or heterogeneous nucleation. CN109226743A discloses a method for reducing the anisotropy of TC4 additive manufacturing by boron alloying modification, which uses nanoparticles to promote heterogeneous nucleation and supercooling, thereby weakening the anisotropy; however, nanoparticles are prone to agglomeration under high-frequency remelting conditions in small molten pools, which in turn become crack initiation sources and damage the plasticity of the alloy.
[0006] In summary, the current methods for controlling anisotropy and microsegregation in additive manufacturing titanium alloys mainly rely on equipment upgrades, external particle modification, or complex hot working processes, which generally suffer from high equipment dependence, long process chains, and high manufacturing costs. Summary of the Invention
[0007] The purpose of this application is to provide a method for in-situ construction of titanium alloy heterostructures by mixing α-rich and β-rich dual powders. By utilizing the non-equilibrium solidification of additive manufacturing and the physical mixing characteristics of Marangoni motion in the molten pool, the intrinsic metallurgical defect of "rapid solidification and micro-segregation in extremely non-equilibrium micro-regions" is transformed into a controllable means of microstructure regulation. While solving the intrinsic metallurgical defects of additive manufacturing such as columnar crystal epitaxial growth and compositional inhomogeneity, this method has the feasibility and scalability for industrial production. It is a scalable, low-threshold, and replicable integrated material-process solution for titanium alloy additive manufacturing.
[0008] To achieve the above objectives, this application provides the following technical solution: The method for in-situ construction of titanium alloy heterostructures by mixing α-rich and β-rich dual powders provided in this application includes the following steps: Step 1: Based on the nominal composition of the selected titanium alloy grade, classify the α-stabilizing elements and β-stabilizing elements. Under the premise that the actual chemical composition of the obtained part meets the nominal composition requirements of the grade after mixing at the preset mass ratio and deposition through additive manufacturing, recalculate and allocate the alloy composition to prepare high-sphericity titanium alloy pre-alloyed powders, denoted as powder A and powder B, respectively. Powder A is a titanium alloy powder rich in α-stabilizing elements, with the composition being titanium and α-stabilizing elements. Powder B is a titanium alloy powder rich in β-stabilizing elements, with the composition being titanium, β-stabilizing elements, and neutral elements. Step 2: Mechanically mix powder A and powder B according to a preset mixing ratio, and vacuum dry to obtain a uniformly mixed bi-alloy powder. Step 3: Fix the deposition substrate onto the forming chamber worktable of the laser-directed energy deposition (L-DED) equipment, evacuate the chamber and refill it with high-purity protective gas; load the dual alloy mixed powder into the powder feeder of the equipment; Step 4: Using a coaxial powder feeding method, laser directional energy deposition printing is performed on the dual alloy mixed powder according to the preset process parameters to obtain titanium alloy components by utilizing the rapid solidification characteristics of the molten pool. During the printing process, the dual-alloy mixed powder melts instantaneously within a laser micro-melt pool. Due to the extremely short pool life and ultra-high solidification cooling rate, the Marangoni convection within the melt cannot achieve complete element homogenization. Consequently, after in-situ non-equilibrium solidification, a heterogeneous structure with continuous chemical composition fluctuations is constructed within the alloy matrix. These chemical composition fluctuations induce strong compositional supercooling, blocking the epitaxial growth of columnar crystals and suppressing the anisotropy of the mechanical properties of the formed part. Simultaneously, fluctuations in the local phase transformation thermodynamic driving force cause the α-rich stable element microregions to transform into high-strength and fine α-phase structures, while the β-rich stable element microregions remain as high-ductility and high-toughness metastable regions. The two intertwine to form a multi-scale heterogeneous structure. This heterogeneous structure gives the alloy a great damage tolerance, and compared to traditional additive manufacturing titanium alloys, its work hardening rate increases by approximately 1.5 times, exhibiting excellent strength-ductility matching.
[0009] Due to the gradual elemental changes within micro-regions caused by fluctuations in chemical composition, the electronic parameters (Bo values of chemical bond order and Md values of d orbital energy levels) of some micro-regions fall into the phase-stable regions of strain-induced martensitic transformation (TRIP) and strain-induced twinning (TWIP). This allows titanium alloy components to not only induce back stress strengthening at heterogeneous phase boundaries during deformation under load, but also to dynamically trigger the synergistic effect of transformation-induced plasticity and twinning-induced plasticity in situ. Through multiple mechanisms, deformation energy is dissipated, significantly reducing the risk of early local instability of the component and significantly improving the plasticity of the alloy.
[0010] Furthermore, elements classified as α-stable include Al (aluminum), C (carbon), and Sn (tin); elements classified as β-stable include Mo (molybdenum), Nb (niobium), V (vanadium), W (tungsten), Ta (tantalum), Re (rhenium), Fe (iron), Co (cobalt), Cr (chromium), Zr (zirconium), and Hf (hafnium); and elements classified as neutral include Si (silicon).
[0011] Furthermore, according to mass percentage, the preset mixing ratio of powder A and powder B is 2:8 to 8:2.
[0012] Furthermore, the raw materials for preparing powder A and powder B are elemental raw materials with a purity of 99.9% or higher. The content of impurities such as O (oxygen), N (nitrogen), H (hydrogen) and Fe (iron) is tested to ensure that the requirements for titanium alloy smelting are met. The elemental raw materials are treated with degreasing, decontamination and drying. Raw materials that are easy to absorb moisture or are easy to oxidize are dried under vacuum or inert atmosphere.
[0013] Furthermore, both powder A and powder B are prepared using vacuum induction melting gas atomization or plasma rotating electrode atomization processes. During the preparation of each powder, the elemental raw materials are distributed and mixed according to the design, and then melted by vacuum induction melting or plasma rotating electrode to form a uniform alloy liquid. Then, they are prepared into pre-alloyed spherical powders by high-pressure gas atomization or centrifugal atomization. The particle size range of powder A is 35μm to 150μm, and the particle size range of powder B is 55μm to 200μm.
[0014] Furthermore, in step two, powder A and powder B are premixed in a three-dimensional powder mixer for 4 to 8 hours. After being mixed evenly, they are dried in a vacuum drying oven at 120°C for 120 minutes to obtain a dual alloy mixed powder.
[0015] Furthermore, in step four, the process parameters for laser directional energy deposition printing are as follows: laser power of 1000W to 2800W, laser scanning speed of 5mm / s to 20mm / s, powder feeding rate of 100g / h to 500g / h, carrier gas and protective gas flow rate of 6L / min to 20L / min, and oxygen content in the forming chamber of less than 30ppm.
[0016] Furthermore, the total content of α-stabilizing elements in powder A is 15% to 35% of the mass of its titanium, and the total content of β-stabilizing elements in powder B is 10% to 30% of the mass of its titanium.
[0017] Furthermore, the deposition substrate is a TA1 pure titanium plate, and the substrate preheating temperature is 50℃~250℃, with the specific temperature adapted according to the thermal properties of the titanium alloy grade.
[0018] The principle of this application is: Utilizing the millisecond-level lifetime and 10 of the tiny molten pool during laser-directed energy deposition process 3 K / s ~ 10 5The ultra-high cooling rate of K / s allows α-rich and β-rich pre-alloyed powders to melt simultaneously in the molten pool. However, limited by the limited mixing capacity of Marangoni convection, non-equilibrium solidification occurs before the atoms are completely homogenized, resulting in continuous microscopic chemical composition fluctuations in situ within the matrix. These fluctuations induce strong compositional supercooling at the solidification front, effectively interrupting the epitaxial growth of coarse columnar crystals induced by directional heat flow, transforming the microstructure into equiaxed crystals. Simultaneously, locally enriched α-stabilizing elements promote the nucleation of fine, dispersed α phases, while enriched β-stabilizing elements cause some regions to solidify into metastable β microregions. In subsequent thermal cycles, the metastable β portion decomposes into extremely fine α phases, while the α phase coarsening is limited by chemical barriers, ultimately forming a multi-scale, multi-morphological heterogeneous microstructure. Furthermore, the continuous gradual change in microstructure leads to a wide range of local d-electron energy level parameters (Bo-Md), causing some metastable micro-regions to fall precisely into the phase stability regions of strain-induced martensitic transformation (TRIP) and strain-induced twinning (TWIP). In addition, the significant mechanical mismatch generated by the multi-scale two-phase heterostructure promotes the accumulation of geometrically necessary dislocations in large quantities at the heterostructure boundary, which excites strong heterostructure deformation-induced stress, thereby providing an extremely high additional work hardening rate and achieving a synergistic improvement in strength and plasticity.
[0019] The technical solution of this application has the following beneficial effects: This application utilizes a method combining dual-powder physical mixing and laser-directed energy deposition to directly blend and print titanium alloy powders rich in α-stabilizing elements (powder A) and β-stabilizing elements (powder B). Leveraging the non-equilibrium solidification characteristics of the molten pool, it transforms the disadvantage of "microscopic segregation" in additive manufacturing into the advantage of "composition modulation." This method overturns the conventional approach relying on heat treatment control, achieving design driven by non-equilibrium and obtaining excellent synergistic microstructure and mechanical properties without complex post-processing. Heterogeneous materials are directly prepared through pre-mixed powder deposition, eliminating the need for multi-bucket powder preparation or complex powder delivery systems, resulting in a short process chain and low equipment modification requirements. This method offers high industrial flexibility and wide adaptability, proving effective for other phase change alloys besides titanium alloys. It is easily and quickly implemented in existing production lines, greatly facilitating low-cost engineering and mass production applications.
[0020] This application utilizes compositional modulation to create an alternating distribution of β-stable microregions and α-reinforcing microregions, along with a multi-scale interface network, thereby stimulating significant back stress strengthening. Simultaneously, the broadening of microregion composition causes some areas to fall into the TRIP or TWIP regions of the Bo-Md diagram, dynamically introducing plastic energy dissipation and work hardening, achieving a synergistic improvement in both strength and plasticity, and increasing the work hardening rate. This compositionally modulated heterostructure can suppress columnar crystal epitaxy and strong texture, reducing anisotropy and performance dispersion. Furthermore, the heterostructure's role in sharing stress and strain improves tolerance to defects such as porosity and lack of fusion, increasing the forming yield and service reliability of components, and reducing reliance on high-cost post-processing methods such as hot isostatic pressing (HIP), thus reducing production cycle time and overall manufacturing costs. Attached Figure Description
[0021] The accompanying drawings, which form part of this application, are used to provide a further understanding of this application. The illustrative embodiments and descriptions of this application are used to explain this application and do not constitute an undue limitation of this application. Wherein: Figure 1 The microstructure and tensile mechanical properties of Example 1 of this application are shown below; (a) is a β grain morphology diagram; (b) is the microstructure of the composition-modulated heterostructure; (c) is the room temperature tensile mechanical property curve along the XY and XZ directions; and (d) is a comparison diagram of the work hardening rate between Example 1 and Comparative Example 1.
[0022] Figure 2 The microstructure and tensile mechanical properties of Example 2 of this application are shown below; (a) is a β grain morphology diagram; (b) is the microstructure of the composition-modulated heterostructure; (c) is the room temperature tensile mechanical property curve along the XY and XZ directions; and (d) is a comparison diagram of the work hardening rate between Example 2 and Comparative Example 1.
[0023] Figure 3 The microstructure and tensile mechanical properties of Example 3 of this application are shown below; (a) is a β-grain morphology diagram; (b) is the microstructure of the composition-modulated heterostructure; (c) is the room temperature tensile mechanical property curve along the XY and XZ directions; and (d) is a comparison diagram of the work hardening rate between Example 3 and Comparative Example 1.
[0024] Figure 4 The microstructure and tensile mechanical properties of Example 4 of this application are shown below; (a) is a β-grain morphology diagram; (b) is the microstructure of the composition-modulated heterostructure; and (c) is the room temperature tensile mechanical property curve along the XY and XZ directions.
[0025] Figure 5 The microstructure and tensile mechanical properties of Comparative Example 1 of this application are shown below; (a) is a β-grain morphology diagram; (b) is the microstructure of the composition-modulated heterostructure; and (c) is the room temperature tensile mechanical property curve along the XY and XZ directions.
[0026] Figure 6 The microstructure and tensile mechanical properties of Comparative Example 2 of this application are shown in the following figures: (a) β grain morphology diagram; (b) microstructure of compositionally modulated heterostructure; (c) room temperature tensile mechanical property curves along the XY and XZ directions.
[0027] Figure 7 This is a performance comparison chart of Ti65 alloy prepared by Example 1 of this application and other processes. Detailed Implementation
[0028] The present application will now be described in detail with reference to the accompanying drawings and embodiments. Various examples are provided by way of explanation and not by way of limitation. In fact, those skilled in the art will recognize that modifications and variations can be made to the present application without departing from the scope or spirit thereof. For example, a feature shown or described as part of one embodiment may be used in another embodiment to produce yet another embodiment. Therefore, it is desirable that the present application encompass such modifications and variations that fall within the scope of the appended claims and their equivalents.
[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this disclosure belongs. The terminology used herein is for the purpose of describing embodiments of this disclosure only and is not intended to limit this disclosure.
[0030] To address the challenges of strong anisotropy, microscopic segregation, and reliance on subsequent heat treatment in laser additive manufacturing of titanium alloys, this application proposes a method for preparing multi-scale composition-modulated heterogeneous titanium alloys. By mechanically mixing and directly depositing pre-alloyed powders rich in α and β stabilizing elements, and utilizing the Marangoni convection and rapid solidification characteristics of the molten pool, a heterogeneous network structure with continuously fluctuating composition and interwoven α / β microregions is spontaneously constructed within the deposited matrix. This structure effectively broadens the local Bo-Md parameter distribution. Under load and deformation, the alloy synergistically stimulates back stress strengthening and TRIP / TWIP energy dissipation mechanisms, not only completely eliminating microstructural anisotropy but also achieving excellent room-temperature and high-temperature strength-plasticity matching, providing a new pathway for low-cost, high-performance applications of additively manufactured titanium alloys.
[0031] A method for in-situ construction of titanium alloy heterostructures by mixing α-rich and β-rich dual powders includes the following steps: Step 1: Prepare two types of titanium alloy pre-alloyed powders; Based on the nominal composition of the selected titanium alloy grade, the α-stabilizing elements and β-stabilizing elements are classified. Under the premise that the actual chemical composition of the resulting part meets the nominal composition requirements of the grade after mixing at a preset mass ratio and undergoing additive manufacturing deposition, the alloy composition is recalculated and allocated to prepare high-sphericity titanium alloy pre-alloyed powders, denoted as powder A and powder B, respectively. Powder A is a titanium alloy powder rich in α-stabilizing elements, consisting of titanium and α-stabilizing elements; powder B is a titanium alloy powder rich in β-stabilizing elements, consisting of titanium, β-stabilizing elements, and neutral elements. Al, C, and Sn are classified as α-stabilizing elements; Mo, Nb, V, W, Ta, Re, Fe, Co, Cr, Zr, and Hf are classified as β-stabilizing elements; Si is classified as a neutral element. The preset mixing ratio of powder A and powder B is 2:8 to 8:2. Both powder A and powder B are prepared using vacuum induction melting gas atomization or plasma rotating electrode atomization processes. During the preparation of each powder, the elemental raw materials are distributed and mixed according to the design, and then melted by vacuum induction melting or plasma rotating electrode to form a uniform alloy liquid. Then, they are prepared into pre-alloyed spherical powders by high-pressure gas atomization or centrifugal atomization. The particle size range of powder A is 35μm to 150μm, and the particle size range of powder B is 55μm to 200μm, ensuring that the sphericity of the powders is ≥95% and the oxygen content is strictly controlled at ≤0.12wt.%. Step 2: Mechanical blending and drying: Accurately weigh powder A and powder B according to the preset mass percentage, pour the weighed powder into the mixing tank of the three-dimensional oscillating mixer, set the mixing speed to 30 rpm to 60 rpm, and the mixing time to 4 h to 8 h, and place the mixed powder in a vacuum drying oven at 120 ℃ for 120 minutes to obtain the dual alloy mixed powder.
[0032] Step 3: Pre-printing processing and device initialization: TA1 pure titanium sheet was selected as the deposition substrate. The surface oxide scale was removed by grinding and the substrate was cleaned with anhydrous ethanol. The chamber was evacuated to negative pressure and then refilled with high-purity argon gas for at least three cleaning cycles to control the oxygen and water vapor content in the chamber to be below 30 ppm. The substrate was preheated to 50℃~250℃ to reduce the thermal stress of the initial deposition layer.
[0033] Step 4: In-situ powder mixing printing and component modulation construction: Using a coaxial powder feeding method, laser directional energy deposition printing is performed on the dual alloy mixed powder according to the preset process parameters, and titanium alloy components are obtained by utilizing the characteristics of rapid solidification of the molten pool. The process parameters for laser-directed energy deposition printing are as follows: laser power of 1000W to 2800W, spot diameter of 1.5mm to 5.0mm, laser scanning speed of 5mm / s to 20mm / s, powder feeding rate of 100g / h to 500g / h, carrier gas and protective gas flow rate of 6L / min to 20L / min, single-layer lifting thickness of 0.1mm to 2.0mm, overlap distance of 0.5mm to 3.0mm, a cross-scanning strategy with an angle of 67° between adjacent deposition layer scan lines is adopted, and the oxygen content in the forming chamber is less than 30ppm.
[0034] Furthermore, the raw materials for preparing powder A and powder B are elemental raw materials with a purity of 99.9% or higher. The content of impurities such as O, N, H and Fe is tested to ensure that the requirements for titanium alloy smelting are met. The elemental raw materials are treated with degreasing, decontamination and drying. Raw materials that are easy to absorb moisture or are easy to oxidize are dried under vacuum or inert atmosphere.
[0035] Furthermore, the total content of α-stabilizing elements in powder A is 15% to 35% of the mass of its titanium, and the total content of β-stabilizing elements in powder B is 10% to 30% of the mass of its titanium.
[0036] This application applies to titanium alloys, where Ti is the matrix element. For alloying elements, Al, Sn, and C are classified as α-stable (or α-tendency) elements, Ta, Nb, Mo, W, Zr, and V are classified as β-stable (or β-tendency) elements, and Si is classified as a neutral element.
[0037] Example 1 A method for in-situ construction of titanium alloy heterostructures by mixing α-rich and β-rich dual powders includes the following steps: Step 1: Prepare titanium alloy powder raw materials; based on the nominal composition of high-temperature near-α titanium alloy Ti65 (Ti-5.9Al-4.0Sn-0.4Si-3.5Zr-0.3Mo-2.0Ta-0.3Nb-1W-0.05C), and ensuring that the overall composition of the part meets the nominal composition of the titanium alloy after mixing and depositing powder A and powder B at a mass ratio of 1:1, the composition of the two pre-alloyed powders is recalculated and allocated, resulting in: Titanium alloy powder rich in α-stabilizing elements (powder A): Ti-11.8Al-8.0Sn-0.1C, where the numbers represent the mass percentage of the element in the total mass of powder A, with the remainder being titanium; Titanium alloy powder rich in β-stabilizing elements (powder B): Ti-0.6Mo-4.0Ta-0.6Nb-7.0Zr-2.0W-0.8Si, where the numbers represent the mass percentage of the element in the total mass of powder B, with the remainder being Ti; the neutral element Si is distributed in powder B. Both powder A and powder B are prepared using vacuum induction melting gas atomization (VIGA) or plasma rotating electrode atomization (PREP) processes to ensure that the powders are pre-alloyed spherical powders; the sphericity of the powders is ≥95% and the oxygen content is ≤0.12wt.%. Specifically, the particle size range of powder A is 35μm to 150μm, and the particle size range of powder B is 55μm to 200μm.
[0038] Step 2: Weigh raw material powder A and powder B at a mass ratio of 1:1 and mix them. Place the mixed powders in a three-dimensional oscillating mixer for mechanical mixing at a mixing speed of 45 rpm for 6 hours. After mixing, place the mixture in a vacuum drying oven at a vacuum degree below 1×10⁻⁶. -1 Drying at 140℃ for 3 hours; Step 3: Select TA1 pure titanium plate as the deposition substrate, grind and clean it and fix it in the forming chamber; alternately evacuate and refill the chamber with high-purity argon three times to ensure that the water and oxygen content is below 30ppm; maintain a slight positive pressure of 200Pa in the chamber and preheat the substrate to 200℃. Step 4: Printing is performed using a coaxial powder feeding method. The process parameters are set as follows: spot diameter is 3mm, laser power is 2000W, scanning speed is 16mm / s, powder feeding rate is 400g / h, carrier gas and protective gas flow rate is 12L / min, carrier gas and protective gas are high-purity argon, single-layer lifting thickness is 0.3mm, overlap distance is 1.7mm, and a cross-scanning strategy with an angle of 67° between adjacent deposition layer scan lines is adopted. The oxygen content in the forming chamber is less than 30ppm.
[0039] The microstructure of the titanium alloy obtained in Example 1 is shown below. Figure 1 (a) and (b) in the examples. From the macroscopic structure, it can be seen that, unlike the coarse epitaxial columnar crystals of Comparative Example 1, due to intense compositional supercooling, the growth of the columnar crystals in this embodiment was completely interrupted, and the structure is dominated by fine equiaxed β grains, such as... Figure 1 As shown in (a) of the image, (a) is a low-magnification microstructure image, showing the morphology of the deposited β grains, with the dashed lines indicating the β grain boundary outlines. Figure 1 As shown in (b), through the combined effect of rapid solidification and limited mixing by Marangoni convection, continuous fluctuations in chemical composition were observed in the sedimentary structure. Microregions rich in α-stabilizing elements were more likely to form fine α-phase reinforced structures, while microregions rich in β-stabilizing elements were more likely to be retained as metastable β regions. The two intertwined to form a multi-scale heterogeneous structure.
[0040] Figure 1 Figure (c) shows the room temperature tensile mechanical property curves of the titanium alloy prepared in this embodiment along the XY and XZ directions. The figure indicates that the tensile strength of the titanium alloy prepared in this embodiment along the XY direction is 1260 MPa, and the plasticity is 10.9%; the tensile strength along the XZ direction is 1265 MPa, and the plasticity is 11.1%, with a tensile strength difference of 0.4%, indicating that the macroscopic anisotropy of the component has been essentially eliminated. The tensile strength of the alloy in the XY direction is increased by 23.0% compared to Comparative Example 1, and the plasticity of the alloy is increased by 41.6% compared to Comparative Example 1; the tensile strength of the alloy in the XZ direction is increased by 16.2% compared to Comparative Example 1, and the plasticity of the alloy is increased by 76.2% compared to Comparative Example 1, achieving a synergistic improvement in strength and plasticity.
[0041] Figure 1Figure (d) shows a comparison of the work hardening rates of Example 1 and Comparative Example 1. The work hardening rate of Example 1 is significantly higher than that of Comparative Example 1, indicating that the alternating distribution of β-stable micro-regions and α-strengthening micro-regions during straining stimulates significant back stress strengthening. Simultaneously, the broadening of micro-region composition causes some areas to fall into the TRIP or TWIP region, dynamically introducing plastic energy dissipation during deformation under load, significantly reducing the risk of early local instability of the component, and significantly improving the plasticity of the alloy.
[0042] like Figure 7 As shown, the mechanical properties of the Ti65 alloy prepared in Example 1 are far superior to those of the Ti65 alloy prepared by hot sintering, forging, heat treatment, rolling and laser energy deposition processes. Figure 7 The processing conditions for Ti65 alloy are as follows: Hot sintering process: The alloy was prepared by spark plasma sintering (SPS) at 1200℃ and 35MPa for 10 minutes. The tensile strength data of the prepared alloy are from the paper. Sisi Tang, et al. Achieving superior high-temperature strength and ductility in near-α titanium alloys by in-situ silicide modulation. Journal of Materials Science & Technology, 2025, 237: 38-53; Forging process: forging in the β-phase region, annealing in the two-phase region, and water cooling treatment; the tensile strength data of the prepared alloy are from the paper. PL NARAYANA, et al. Tensile properties of a newly developed high-temperature titanium alloy at room temperature and 650 C [J]. MaterialsScience and Engineering: A, 2018, 718: 287-291; Heat treatment process: Double heat treatment involving holding at 1015℃ for 2 hours and air cooling, followed by holding at 700℃ for 2 hours and air cooling; the tensile strength data of the prepared alloy comes from the paper. Tao Wang, et al. The effect of microstructure on tensile properties,deformation mechanisms and fracture models of TG6 high temperature titanium alloy. Materials Science and Engineering: A, 2011, 528.6: 2370-2379; Rolling process: After homogenization at 1100℃ for 2 hours, the alloy was rolled at 1030℃ with a large deformation of 75%; the tensile strength data of the prepared alloy are from the paper. Juan Li, et al. Development of Ti-Al-Ta-Nb-(Re) near-α hightemperature titanium alloy: Microstructure, thermal stability and mechanical properties. Journal of MaterialsScience & Technology, 2022, 109: 1-11; Laser energy deposition process: laser-directed energy deposition was performed using a laser power of 2500W and a scanning speed of 10mm / s; the tensile strength data of the prepared alloy are from the paper. Junfeng Sun, et al. Evolution of microstructure and mechanicalproperties of Ti65 high-temperature titanium alloy after additive manufacturing and annealing. Materials Science and Engineering: A, 2024, 913:147002.
[0043] Example 2 In steps one and two of this embodiment, powder A and powder B are mixed at a mass ratio of 8:2.
[0044] A method for in-situ construction of titanium alloy heterostructures by mixing α-rich and β-rich dual powders includes the following steps: Step 1: Prepare titanium alloy powder raw materials; based on the nominal composition of high-temperature near-α titanium alloy Ti65 (Ti-5.9Al-4Sn-0.4Si-3.5Zr-0.3Mo-2Ta-0.3Nb-1W-0.05C), and ensuring that the overall composition of the part meets the nominal composition of the titanium alloy after mixing and depositing powder A and powder B at a mass ratio of 8:2, the composition of the two pre-alloyed powders is recalculated and allocated, resulting in: Titanium alloy powder rich in α-stabilizing elements (powder A): Ti-7.38Al-5.0Sn-0.06C, where the numbers represent the mass percentage of each element in the total mass of powder A, with the remainder being titanium; Titanium alloy powder rich in β-stabilizing elements (powder B): Ti-17.5Zr-10Ta-5W-2Si-1.5Nb-1.5Mo, where the numbers represent the mass percentage of each element in the total mass of powder B, with the remainder being titanium; Neutral element Si is distributed in powder B; The preparation methods and particle size requirements for both powders are the same as in Example 1.
[0045] Step 2: Weigh raw material powder A and powder B at a mass ratio of 8:2 and mix them. Place the mixed powders in a three-dimensional oscillating mixer for mechanical blending at a mixing speed of 45 rpm for 6 hours. After mixing, place the mixture in a vacuum drying oven at a vacuum degree below 1×10⁻⁶. -1 Drying at 140℃ for 3 hours.
[0046] Steps three and four are exactly the same as in Example 1.
[0047] Figure 2 In Example 2, (a) shows the β-grain morphology of the titanium alloy, and (b) shows the microstructure of the compositionally modulated heterogeneous structure. Due to the significantly increased proportion of powder A in this example, the microstructure transforms into a network of "hard zones" composed of numerous coarse and high-strength primary α-phases, accompanied by smaller metastable regions, successfully forming a biphase heterogeneous distribution, such as... Figure 2 As shown in (b) of the diagram. Meanwhile, as... Figure 2 As shown in (a), the structure also completely blocked the growth of epitaxial columnar crystals due to the influence of the large interface kinetic coefficient. The microstructure is dominated by equiaxed β grains, which shows that the dual powder mixing strategy is effective in suppressing columnar crystals.
[0048] Figure 2(c) shows the room temperature tensile mechanical property curves of the titanium alloy prepared in this embodiment along the XY and XZ directions. Its tensile strength along the XY direction is 1280 MPa, and its plasticity is 9.1%; the tensile strength along the XZ direction is 1276 MPa, and its plasticity is 9.3%, with a tensile strength difference of 0.31%, indicating isotropic mechanical properties. The tensile strength of the alloy along the XY direction is 25.0% higher than that of Comparative Example 1, and its room temperature plasticity is 18.2% higher. The tensile strength of the alloy along the XZ direction is 17.2% higher than that of Comparative Example 1, and its room temperature plasticity is 47.6% higher. Compared to Example 1, the plasticity of the alloy slightly decreases due to the increase in the "hard zone" formed by the primary α. Figure 2 As shown in (d), the work hardening rate of Example 2 is still higher than that of Comparative Example 1. This indicates that although the proportion of α-rich / β-rich microregions has changed, the heterostructure formed by their interweaving still stimulates significant back stress strengthening. At the same time, the broadening of microregion composition allows some areas to still fall into the TRIP / TWIP region, providing an additional plastic energy dissipation mechanism.
[0049] Example 3 In steps one and two of this embodiment, powder A and powder B are mixed at a mass ratio of 2:8.
[0050] A method for in-situ construction of titanium alloy heterostructures by mixing α-rich and β-rich dual powders includes the following steps: Step 1: Prepare titanium alloy powder raw materials; based on the nominal composition of high-temperature near-α titanium alloy Ti65 (Ti-5.9Al-4.0Sn-0.4Si-3.5Zr-0.3Mo-2.0Ta-0.3Nb-1.0W-0.05C), and ensuring that the overall composition of the part meets the nominal composition of the titanium alloy after mixing and depositing powder A and powder B at a mass ratio of 2:8, the composition of the two pre-alloyed powders is recalculated and allocated to obtain: Titanium alloy powder rich in α-stabilizing elements (powder A): Ti-29.5Al-20.0Sn-0.25C, where the numbers represent the mass percentage of this element in the total mass of powder A, with the remainder being titanium; Titanium alloy powder rich in β-stabilizing elements (powder B): Ti-4.38Zr-0.38Mo-2.5Ta-0.38Nb-1.25W-0.5Si, where the numbers represent the mass percentage of this element in the total mass of powder B, with the remainder being titanium; Neutral element Si is distributed in powder B; The preparation methods and particle size requirements for both powders are the same as in Example 1.
[0051] Step 2: Weigh raw material powder A and powder B at a mass ratio of 2:8 and mix them. Place the mixed powders in a three-dimensional oscillating mixer for mechanical blending at a mixing speed of 45 rpm for 6 hours. After mixing, place the mixture in a vacuum drying oven at a vacuum degree below 1×10⁻⁶. -1 Drying at 140℃ for 3 hours.
[0052] Steps three and four are exactly the same as in Example 1.
[0053] The alloy obtained in this embodiment is a composition-modulated heterostructure dominated by β-rich microregions, such as... Figure 3 As shown in (b), the α-rich microregions and β-rich microregions are alternately distributed, the interface between the α phase and the β phase is clear, the ratio of soft and hard regions is balanced, and no single phase is excessively dominant, forming a heterogeneous structure of moderate scale. Figure 3 The β grain morphology in (a) shows that strong compositional supercooling still blocked the growth of columnar β grains, and the microstructure was dominated by equiaxed β grains, which laid the microstructure basis for isotropic mechanical properties. Figure 3 (c) Mechanical tests show that the tensile strength along the XY direction is 1228 MPa, and the plasticity is 11.7%; the tensile strength along the XZ direction is 1200 MPa, and the plasticity is 11.4%, with a tensile strength difference of 2.28%, indicating isotropic mechanical properties. The tensile strength of the alloy along the XY direction is 19.9% higher than that of Comparative Example 1, and the room temperature plasticity is 52.0% higher. The tensile strength along the XZ direction is 10.2% higher than that of Comparative Example 1, and the room temperature plasticity is 81.0% higher. Compared to Example 1, the alloy strength is slightly lower due to the increase in the β-rich metastable region. The increase in work hardening rate still indicates that back stress strengthening and the potential TRIP / TWIP synergistic effect are more easily exerted simultaneously, thus obtaining a better strength-plasticity match, such as... Figure 3 As shown in (d) in the figure.
[0054] The raw materials in Examples 1-3 are the same, the only difference being the ratio of powder A and powder B. Their microstructure characteristics and mechanical properties are summarized in Table 1.
[0055] Table 1. Summary of Microstructure Characteristics and Mechanical Performance of Examples 1-3
[0056] Compared to Comparative Example 1, the tensile strength and room temperature plasticity improvement rates of the alloys in Examples 1-3 are summarized in Table 2. The tensile strength improvement rate is the average of the XY and XZ tensile strength improvement rates, and the plasticity improvement rate is the average of the XY and XZ plasticity improvement rates.
[0057] Table 2. Tensile strength and room temperature plasticity improvement rates of Examples 1-3 compared to Comparative Example 1
[0058] As can be seen from the microstructure characteristics of Examples 1-3, the powder ratio directly determines the proportion, size, and distribution morphology of the soft and hard regions in the heterogeneous structure. From the mechanical properties, it can be seen that the XY and XZ tensile strengths of titanium alloy Ti65 increase with the increase of powder A proportion, while its XY and XZ plasticity increases with the increase of powder B proportion, and both remain isotropic. This indicates that by adjusting the powder ratio, the microstructure and mechanical properties of titanium alloys can be controllably adjusted, achieving on-demand matching. This application provides a scalable, low-barrier, and replicable integrated material-process solution for titanium alloy additive manufacturing.
[0059] Example 4 In this embodiment, conventional dual-phase titanium alloy TC4 (Ti-6Al-4V) is used.
[0060] A method for in-situ construction of titanium alloy heterostructures by mixing α-rich and β-rich dual powders includes the following steps: Step 1: Prepare titanium alloy powder raw materials; the nominal composition of conventional duplex titanium alloy TC4 is Ti-6Al-4V. Assuming that powder A and powder B are mixed and deposited at a 1:1 mass ratio, and the overall composition of the part meets the nominal composition of the titanium alloy, the composition of the two pre-alloyed powders is recalculated and allocated, resulting in: Titanium alloy powder rich in α-stabilizing elements (powder A): Ti-12Al, where the number indicates the mass percentage of Al in the total mass of powder B, and the remainder is titanium, i.e., 88%; Titanium alloy powder rich in β-stabilizing elements (powder B): Ti-8V, where the number indicates the mass percentage of V in the total mass of powder B, and the remainder is titanium, i.e., 92%; The preparation methods and particle size requirements for both powders are the same as in Example 1.
[0061] Step 2: Referring to Step 2 in Example 1, weigh the two powders mentioned above at a mass ratio of 1:1 and mix them.
[0062] Step 3: Select TA1 pure titanium plate as the deposition substrate; alternately evacuate and refill the chamber with high-purity argon three times to ensure that the water and oxygen content is below 30ppm; maintain a slight positive pressure of 200Pa in the chamber; and preheat the substrate to 150℃ to match the thermal properties of TC4 alloy. Step 4: Printing is performed using a coaxial powder feeding method. To adapt to the thermal properties of TC4 alloy, the process parameters are set as follows: laser power 2000W, scanning speed 16mm / s, powder feeding rate 400g / h, carrier gas and protective gas flow rate 12L / min, and high-purity argon gas as the carrier gas and protective gas.
[0063] like Figure 4 As shown in (b) of this embodiment, the deposited state of the TC4 alloy also exhibits fluctuations in chemical composition due to rapid solidification and limited mixing, forming heterogeneous structural units interwoven with α-rich / β-rich microregions; Figure 4 As shown in (a), the macroscopic columnar epitaxial growth is weakened, and the texture and anisotropy are reduced. Figure 4 (c) The room temperature tensile mechanical property curves of the TC4 alloy prepared in this embodiment along the XY and XZ directions. The mechanical test shows that the tensile strength along the XY direction is 1117 MPa and the plasticity is 11.1%; the tensile strength along the XZ direction is 1100 MPa and the plasticity is 11.4%, and the mechanical properties are isotropic.
[0064] Unlike the high-temperature near-α titanium alloys of Examples 1-3, Example 4 uses a conventional dual-phase titanium alloy, proving that the method of this application can also be used for ordinary titanium alloys, indicating that the method of this application has universality.
[0065] Comparative Example 1 This comparative example uses a traditional additive manufacturing process to directly print Ti65 powder to prepare titanium alloys. That is, compared to this application, there is no step of redistributing or mixing the two powders.
[0066] A method for preparing titanium alloy Ti65 includes the following steps: S1. Commercially available, uniformly composed single Ti65 pre-alloyed spherical powder was directly used as the raw material. Its nominal composition met the requirements of Ti-5.9Al-4Sn-0.4Si-3.5Zr-0.3Mo-2Ta-0.3Nb-1W-0.05C. The powder particle size and morphology requirements were the same as in Example 1. The powder was subjected to conventional vacuum drying to obtain the raw material powder. S2. The pre-printing treatment and L-DED deposition molding process parameters are exactly the same as steps three and four of Example 1.
[0067] Figure 5 (b) shows the microstructure of the composition-modulated heterostructure in Comparative Example 1. Because a single powder with uniform composition was used, chemical composition fluctuations could not be induced in the molten pool. Extremely coarse epitaxial columnar crystals, penetrating several deposition layers, grew within the component along the temperature gradient direction (Z-axis). The intracrystalline structure was a basket-like α phase with large dimensions, lacking heterogeneous "soft / hard" micro-region interweaving, as... Figure 5 As shown in (a) of the diagram. Figure 5(c) shows the room temperature tensile mechanical property curves of the titanium alloy prepared in this comparative example along the XY and XZ directions. The results show that its tensile strength along the XY direction is 1024 MPa and its plasticity is 7.7%; its tensile strength along the XZ direction is 1089 MPa and its plasticity is 6.3%, with a tensile strength difference of 6.3%, and its mechanical properties exhibit anisotropy.
[0068] The above results indicate that the component possesses typical additive manufacturing mechanical properties, namely severe macroscopic mechanical anisotropy. Furthermore, due to the lack of back stress strengthening and TRIP / TWIP energy dissipation mechanisms induced by composition modulation, its overall room temperature strength and plasticity are lower than those of Example 1.
[0069] Comparative Example 2 In this comparative example, titanium alloy Ti65 was prepared using pure elemental powder as raw material.
[0070] A method for preparing titanium alloy Ti65 includes the following steps: S1. Based on the nominal composition of the high-temperature near-α titanium alloy Ti65, Ti-5.9Al-4Sn-0.4Si-3.5Zr-0.3Mo-2Ta-0.3Nb-1W-0.05C, prepare titanium alloy powder raw materials. The powder raw materials are high-purity pure Ti powder, pure Al powder, pure Sn powder, pure Zr powder, pure Ta powder, pure Nb powder, pure Mo powder, pure W powder and pure C powder, which are all elemental powders. S2. Weigh the above-mentioned elemental powders strictly according to the nominal composition ratio of titanium alloy Ti65 and perform extremely thorough mechanical mixing and vacuum drying. S3. The pre-printing treatment and L-DED deposition molding process parameters are exactly the same as steps three and four of Example 1.
[0071] Figure 6 (a) shows the β-grain morphology of the titanium alloy prepared in Comparative Example 2, which did not form a "continuous and usable" compositional modulation morphology; macroscopically, the epitaxial growth inhibition effect of columnar crystals was weak, and the directional differences in microstructure and properties were more obvious, such as... Figure 6 (b) shows that the melting point, density and melting / diffusion behavior of each elemental powder are quite different. In addition, the life of the L-DED micro-melt pool is extremely short and the solidification cooling rate is high. The mixed elemental powder is prone to asynchronous melting and local composition fluctuations in the molten pool. The deposited structure often shows stronger random segregation and higher sensitivity to inclusions / defects (such as incompletely melted particles, oxide inclusions and pores). Figure 6The mechanical test results of (c) show that the strength-plasticity synergy and work hardening ability of this comparative example are lower than those of Example 1. Its tensile strength along the XY direction is 1099 MPa and its plasticity is 7.3%; its tensile strength along the XZ direction is 1133 MPa and its plasticity is 6.3%, and its batch stability and molding reliability are relatively poor.
[0072] Comparative Example 1 demonstrates that the composition of the pre-alloyed powder is absolutely uniform, thus eliminating the possibility of constructing heterogeneous structures in situ using microsegregation in additive manufacturing. Comparative Example 2, using pure elemental powder instead of the pre-alloyed powder, suffers from uncontrolled melt pool due to physical asynchrony, and random segregation and defect sensitivity further worsen the performance. In step one of this application, pre-alloyed spherical powders (powder A and powder B) are first prepared. These powders possess uniform chemical composition and stable phase composition, avoiding the asynchronous melting and random segregation problems caused by differences in melting point, density, and oxidation sensitivity of pure elemental powders. This lays the material foundation for the subsequent synchronous melting and in-situ controllable heterogeneous structure construction after mixing the two powders. Furthermore, by recalculating and allocating the composition of the two pre-alloyed powders, powder A is enriched with α-stabilizing elements, and powder B is enriched with β-stabilizing elements. Therefore, in subsequent steps, only the mixing ratio of the two powders needs to be adjusted to achieve the controllable design of the heterogeneous structure.
[0073] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.
Claims
1. A method for in-situ construction of titanium alloy heterostructures by mixing α-rich and β-rich dual powders, characterized in that, Includes the following steps: Step 1: Based on the nominal composition of the selected titanium alloy grade, classify the α-stabilizing elements and β-stabilizing elements and calculate the composition according to the preset mixing ratio to prepare high-sphericity titanium alloy pre-alloyed powders, denoted as powder A and powder B respectively. Al, C, and Sn are classified as α-stabilizing elements; Mo, Nb, V, W, Ta, Re, Fe, Co, Cr, Zr, and Hf are classified as β-stabilizing elements; Si is classified as a neutral element. Powder A is a titanium alloy powder rich in α-stabilizing elements, with a composition of titanium and α-stabilizing elements; Powder B is a titanium alloy powder rich in β-stabilizing elements, with a composition of titanium, β-stabilizing elements, and neutral elements. Step 2: Mechanically mix powder A and powder B according to a preset mixing ratio, and vacuum dry to obtain a uniformly mixed bi-alloy powder. Step 3: Fix the deposition substrate onto the forming chamber worktable of the laser directional energy deposition equipment, evacuate the chamber and refill it with high-purity protective gas; load the dual alloy mixed powder into the powder feeder of the equipment; Step 4: Using a coaxial powder feeding method, laser directional energy deposition printing is performed on the dual alloy mixed powder according to the preset process parameters to obtain titanium alloy components by utilizing the rapid solidification characteristics of the molten pool.
2. The method for in-situ construction of titanium alloy heterostructures by mixing α-rich and β-rich dual powders according to claim 1, characterized in that: According to the mass percentage, the preset mixing ratio of powder A and powder B is 2:8 to 8:
2.
3. The method for in-situ construction of titanium alloy heterostructures by mixing α-rich and β-rich dual powders according to claim 1, characterized in that: The raw materials for preparing powder A and powder B are elemental raw materials with a purity of 99.9% or higher, and the elemental raw materials are subjected to degreasing, decontamination and drying treatment.
4. The method for in-situ construction of titanium alloy heterostructures by mixing α-rich and β-rich dual powders according to claim 1, characterized in that: Powder A has a particle size range of 35μm to 150μm, and powder B has a particle size range of 55μm to 200μm.
5. The method for in-situ construction of titanium alloy heterostructures by mixing α-rich and β-rich dual powders according to claim 1, characterized in that: Both powder A and powder B are prepared using vacuum induction melting gas atomization or plasma rotating electrode atomization processes. During the preparation of each powder, the elemental raw materials are distributed and mixed according to the design, and then melted by vacuum induction melting or plasma rotating electrode to form a uniform alloy liquid. Finally, they are prepared into pre-alloyed spherical powders by high-pressure gas atomization or centrifugal atomization.
6. The method for in-situ construction of titanium alloy heterostructures by mixing α-rich and β-rich dual powders according to claim 1, characterized in that: In step two, powder A and powder B are premixed in a three-dimensional powder mixer for 4 to 8 hours. After mixing, they are dried in a vacuum drying oven at 120°C for 120 minutes to obtain a dual alloy mixed powder.
7. The method for in-situ construction of titanium alloy heterostructures by mixing α-rich and β-rich dual powders according to claim 1, characterized in that: In step four, the process parameters for laser directional energy deposition printing are as follows: laser power of 1000W to 2800W, spot diameter of 1.5mm to 5.0mm, laser scanning speed of 5mm / s to 20mm / s, powder feeding rate of 100g / h to 500g / h, carrier gas and protective gas flow rate of 6L / min to 20L / min, single-layer lifting thickness of 0.1mm to 2.0mm, and oxygen content in the forming chamber of less than 30ppm.
8. The method for in-situ construction of titanium alloy heterostructures by mixing α-rich and β-rich dual powders according to claim 1, characterized in that: The deposition substrate is a TA1 pure titanium plate, and the substrate preheating temperature is 50℃~250℃.
Citation Information
Patent Citations
Method for utilizing boron alloying metamorphism to reduce anisotropy of TC4 additive manufacturing
CN109226743A
Electric arc additive manufacturing method for assisting in titanium alloy grain refinement through coaxial ultrasound
CN119634891A
Nano twin crystal oxygen-containing titanium alloy based on additive manufacturing technology and preparation method of nano twin crystal oxygen-containing titanium alloy
CN119733848A
High-temperature and high-strength titanium alloy and additive preparation method thereof
CN114635056A
Ti60-Ti2AlNb gradient titanium alloy and additive manufacturing method thereof
CN118422010A